The Optimization of Ecological and Economic Systems is on the Basis of the Antysypatyvne Management (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The author singled out stages of implementation the antysypatyv management of ecological and economic system of enterprises. The author analyzes the main advantages and disadvantages of using the method of «decision tree» in the antysypatyv management. There are formed the antysypatyv management modelecological and economic system and test it in the target company.
Keywords: the antysypatyv management, ecological and economic system of the enterprise, optimization, method of «decision tree».